Phenotypic characterisation of Alambadi cattle—An unexplored indigenous population of south India - PARAMESWARI, S; KARTHICKEYAN, S M K; ARUNACHALAM, K; GOPINATHAN, A (The Indian Journal of Animal Sciences, 2021)
Alambadi is one of the draught cattle of south India, distributed unevenly in the hilly tracts of Dharmapuri and Krishnagiri districts of Tamil Nadu and bordering Karnataka, with varying densities. It is a medium-sized animal, with the typical coat colour of iron-grey and distribution of white patches around eyes, above muzzle. The horns were cylindrical, slate-coloured, sloping backwards, spreading sideways and upwards, with a slightly forward slope at the upper half of the horns and ending with a pointed tip. The overall means for body length, chest girth and height at withers of adult bulls, bullocks and cows were 122.96±2.37, 145.50±2.97 and 120.63±1.35; 133.96±2.18, 168.15±2.20 and 134.41±2.30; and 127.52±0.47, 152.08±0.48 and 121.39±0.30 cm respectively. The average body weight of adult bulls, bullocks and cows were estimated as 293.96, 376.73 and 312.09 kg respectively. The means for daily partial milk yield, lactation length and estimated lactation milk yield were 2.60±0.01 kg, 171.16 days and 432.30 kg respectively. The overall mean fat, SNF, protein and total solids contents in raw milk were 3.58±0.13, 8.46±0.60, 3.22±0.05 and 12.01±0.13% respectively. The average age at first oestrus, age at first calving and calving interval of Alambadi cows were 3.33±0.07, 4.46±0.08 and 1.47±0.06 years, respectively. The population of Alambadi cattle (5,273) is categorized as ‘not at risk’.